Big data in small slices : data visualization for communicators - Finch-Claydon, Dianne M. (New York : Routledge, 2021)
"This book offers an engaging and accessible introduction to data visualization for communicators, covering everything from data collection and analysis to the creation of effective data visuals. Straying from the typical "how to visualize data" genre often written for technical audiences, Big Data in Small Slices offers those new to data and visualization the opportunity to better understand data itself. Using the concept of the "Data Backstory", each chapter features discussions with experts who produce datasets in their daily work, from marine scientists to paediatricians and city government officials, exploring how they collect and produce datasets. The reader is guided through the process of designing effective visualizations based on this data, delving into how datasets are produced and vetted and how to assess their weaknesses and strengths, ultimately offering readers the knowledge needed to produce their own effective data visuals. This book is an invaluable resource for anyone interested in data visualisation and storytelling, from journalism and communications students to public relations professionals"--
Introduction -- The canary in the coal mine -- Sea of butterflies -- Parasites and armed rebels -- Open city, open data -- Index.
Includes bibliographical references and index.
Keywords: Visual communication; Information visualization